A Review of Recent Advances in Biomass Pyrolysis - Wang, Guanyu; Dai, Yujie; Yang, Haiping; Xiong, Qingang; Wang, Kaige; Zhou, Jinsong; Li, Yunchao; Wang, Shurong (Energy & fuels, 2020)
Pyrolysis has created many (and will open more) possibilities for high-value utilization of biomass. To obtain the optimal amount of desired pyrolysis products, especially high-quality bio-oil, a great deal of effort has been conducted in both academia in the past few decades, to clarify fundamental mechanisms of biomass pyrolysis and design efficient relevant technical processes. This paper comprehensively reviews recent advances in both fundamental studies and technology applications of biomass pyrolysis. First, pyrolysis mechanisms of real biomass and its major components, the reactor-scale simulation of biomass pyrolysis, and applications of pyrolysis products are discussed. Then, according to the requirements imposed to improve the physicochemical properties of respective pyrolysis products, relevant optimization and regulation methods for biomass pyrolysis process are reviewed. Previous research has indicated that biomass copyrolysis with other feedstock can not only enhance physicochemical properties of pyrolysis products but also effectively realize recycling of wastes. Thus, an in-depth discussion of recent advances in biomass copyrolysis with four different feedstocks (i.e., coal, plastics, tires, and sludge) is covered in this Review. As an indispensable component of general biomass pyrolysis, recent activities of catalytic biomass pyrolysis are also summarized, including new catalytic pyrolysis processes such as catalytic hydropyrolysis and catalytic copyrolysis. Besides, two novel heating approaches (microwave heating and solar heating) for biomass pyrolysis are described, and their features are compared with the conventional heating method. Finally, this Review is concluded with perspectives for future directions of biomass pyrolysis.